INFLUENCE OF GREEN SUPPLY CHAIN MANAGEMENT ON THE PERFORMANCE OF CHINA FURNITURE PRODUCTION COMPANY - Li, Jiantao; Maozhu, Jin (Journal of Buddhist Education and Research (JBER), 2023)
With the rapid development of economy, green supply chain management has gradually entered the human perspective. Its realization is conducive to enterprise brand building, enterprises reduce costs and enterprises bypass green barriers, help enterprises to occupy the advantage in the fierce market competition, improve the comprehensive competitiveness. Under the guidance of the theoretical basis related to sustainable development, this study selected 4 Chinese furniture manufacturers already listed in China as the research objects, excavated the root cause of the inefficiency of green supply chain enterprises from the perspective of management and environment, and identified the improvement strategy and the influence mechanism of exogenous environmental variables. Explore the factors affecting enterprise performance change; put forward reasonable and effective suggestions for strengthening green supply chain management, improving enterprise development environment and improving production efficiency of green supply chain.